Haematopoietic stem cell transplantation in adult soft-tissue sarcoma: an analysis from the European Society for Blood and Marrow Transplantation. Issue 5 (23rd October 2020) - Heilig, Christoph E; Badoglio, Manuela; Labopin, Myriam; Fröhling, Stefan; Secondino, Simona; Heinz, Jürgen; Nicolas-Virelizier, Emmanuelle; Blaise, Didier; Korenbaum, Clément; Santoro, Armando; Verbeek, Mareike; Krüger, William; et al.
Abstract : Background: The role of high-dose chemotherapy with autologous stem cell transplantation (ASCT) in the treatment of soft-tissue sarcoma (STS) remains an unsettled issue. Prospective clinical trials failed to prove a benefit of the procedure but were limited by small and heterogeneous patient cohorts. Thus, it is unknown if ASCT may be a valuable treatment option in specific patient subgroups. Methods: The purpose of this study was to investigate the value of ASCT according to histological subtype in STS patients who were registered in the European Society for Blood and Marrow Transplantation database between 1996 and 2016. Results: Median progression-free (PFS) and overall survival (OS) in the entire cohort of 338 patients were 8.3 and 19.8 months, respectively, and PFS and OS at 5 years were 13% and 25%, respectively. Analysis of outcomes in different subgroups showed that younger age, better remission status before transplantation and melphalan-based preparative regimen were predictive of benefit from ASCT, whereas histology and grading had no statistically significant impact. Conclusions: Outcomes after ASCT compared favorably to those of recent trials on conventional chemotherapies and targeted therapies in STS, including histology-tailored approaches. ASCT, thus, should be reinvestigated in clinical trials focusing on defined patient subgroups.